Pengembangan Media Video Pembelajaran Materi Kebutuhan Manusia dan Kelangkaan Sumber Daya Berbantu Kahoot di Kelas VII SMP Muallimin Wonodadi Blitar - Irma Yunita; Hendra Pratama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Learning media are physical tools that deliver information or learning materials to students. Educational videos have become one of the aids used in teaching and learning activities. These videos can support the learning process by conveying materials through the use of technology. Therefore, the researcher was interested in developing a medium that can be both heard and seen by students to help them better understand the subject matter. This study employed a Research and Development (R&D) approach using the Borg & Gall development model, which consists of ten development steps. The development process included initial information gathering, planning, initial product development, expert validation tests, initial product revisions, small-scale testing, second product revisions, large-scale field testing, final product refinement, and product dissemination. The results showed that the validity test of the learning media yielded a percentage of 94% from media experts, 96% from subject matter experts, 94% from language experts, and 94% from teachers. Meanwhile, the product effectiveness test using a Paired Sample T-Test showed a significance value of 0.000, which is lower than the threshold of 0.05. This indicates that the alternative hypothesis is accepted, proving a significant difference in student learning outcomes before and after using the educational video. Therefore, it can be concluded that the educational video on